2021
DOI: 10.3390/cells10113003
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Mitochondrial Metabolism as a Strategy to Treat Senescence

Abstract: Mitochondria are one of organelles that undergo significant changes associated with senescence. An increase in mitochondrial size is observed in senescent cells, and this increase is ascribed to the accumulation of dysfunctional mitochondria that generate excessive reactive oxygen species (ROS). Such dysfunctional mitochondria are prime targets for ROS-induced damage, which leads to the deterioration of oxidative phosphorylation and increased dependence on glycolysis as an energy source. Based on findings indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 103 publications
(161 reference statements)
3
17
0
Order By: Relevance
“…We were able to detect increased TCA cycle activity by performing flux measurements using radioactive-labeled glucose, and we measured enhanced basal and maximal respiration as well as higher mitochondrial ATP production by monitoring the oxygen consumption in Seahorse analyses. These data point to an unexpected enhancement of mitochondrial function in senescent endothelial cells since, so far, senescent phenotypes are often characterized by mitochondrial dysfunction and the deterioration of oxidative phosphorylation [ 13 ]. The observed increase in respiratory function may be related to an enhanced activity of PDH, which can be concluded from its decreased phosphorylation at Ser293 and which allows an increased shuttling of pyruvate to the TCA cycle via acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were able to detect increased TCA cycle activity by performing flux measurements using radioactive-labeled glucose, and we measured enhanced basal and maximal respiration as well as higher mitochondrial ATP production by monitoring the oxygen consumption in Seahorse analyses. These data point to an unexpected enhancement of mitochondrial function in senescent endothelial cells since, so far, senescent phenotypes are often characterized by mitochondrial dysfunction and the deterioration of oxidative phosphorylation [ 13 ]. The observed increase in respiratory function may be related to an enhanced activity of PDH, which can be concluded from its decreased phosphorylation at Ser293 and which allows an increased shuttling of pyruvate to the TCA cycle via acetyl-CoA.…”
Section: Discussionmentioning
confidence: 99%
“…It may be driven by the disruption of metabolic homeostasis, for instance, by reduced cytosolic NAD+/NADH ratio, high glucose or insufficient autophagy, and is, on the other hand, characterized by intracellular metabolic reprogramming, which may then promote senescence in feedback loops [ 11 ]. For instance, a shift towards glycolysis and diversion of pyruvate away from oxidative metabolism, changes in lipid metabolism, including lipid droplet formation and enhanced β-oxidation of fatty acids, as well as an increase in mitochondrial and lysosomal mass associated with organelle dysfunction, have been observed in senescent cells [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…For each cell line, we compared the condition-specific iCell networks of all time points together (i.e., D4 vs D0, D33 vs D4, and D33 vs D0). For all cell lines, we observed that the top 10% of the most “perturbed” genes were enriched in “ADIPOGENESIS” (a pathway observed in senescent fibroblasts [38]) and “OXIDATIVE PHOSPHORYLATION” (OxPhos) (a pathway commonly dysregulated in senescence, linked to mitochondrial dysfunction which is among the hallmarks of ageing and has been proposed as a targeting strategy to treat senescent cells [39, 40]) at different contrasts (Fig 5.C). Then, we compared the local topology of genes between the condition-specific iCell networks of different cell lines, but at matching time points (e.g., SKMEL30_D0 vs MELJUSO_D0).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies revealed that cellular senescence is associated with mitochondrial defects [37][38][39]. We therefore assessed the effects of Aβ on mitochondrial functions in HMC3 cells.…”
Section: Aβ Accelerated Mitochondrial Dysfunction In Microgliamentioning
confidence: 99%